Factors influencing the resilience of carers of individuals with dementia. Issue 4 (18th October 2013) - Cherry, MG; Salmon, P; Dickson, JM; Powell, D; Sikdar, S; Ablett, J
Summary: Most individuals with dementia live in the community, receiving care from family or lay carers. Carers' wellbeing, and the quality of the care they provide, depends on their resilience in the face of the challenges associated with caring for someone with dementia. However, factors associated with carers' resilience are not yet fully understood. The aim of this review is to present a narrative synthesis of factors, materials and resources associated with carers' resilience. Electronic and hand searches identified relevant published literature, which was narratively synthesized. A framework consisting of three inter-related domains of factors influencing carers' resilience emerged, encompassing: social and cultural factors; properties of the care relationship; and carers' psychological factors. Holistic assessment based on this framework can help practitioners to identify vulnerable carers and to target help on factors that help to make them vulnerable but that are amenable to change.